Integration of Fethullah Gulen's Thought for The Development of Multicultural Islamic Education in Indonesia - Purnomo, Sutrimo; Kusumawanti, Windhariyati Dyah; Chedo, Zainab (International Journal of Islamic Studies Higher Education, 2023)
Constructing the awareness of coexisting peacefully regardless of differences in religion, ethnicity or language is an absolute thing that must be instilled in Indonesia from an early age in the younger generation as a multicultural country. If there is no such efforts to construct that awareness, acts of intolerance will continue to develop and have even penetrated the younger generation of students. For this reason, awareness of the importance of multiculturalism needs to be instilled, including through multicultural Islamic education. This article aims to discuss Fethullah Gulen's thoughts on Islamic education and how it is integrated into multicultural Islamic education in Indonesia. This study uses a qualitative method with a content analysis approach. The main data sources are taken from Islamic education theories and two main books (Toward a Global Civilization of Love and Tolerance and Multicultural Education: Issues and Perspectives) and are supported by 20 related journal articles. All data were analyzed using the Miles and Huberman technique. The findings show that there are nine themes of integration for the development of multicultural Islamic education. The nine themes are grouped into three elements, namely: Love (love for God, compassion for human beings (humanism), forgiveness, love for science, and love for nature); Tolerance and Dialogue (respect for differences in thoughts and religions, love as the basis for tolerance, and dialogue as a means of building tolerance). These findings can be used as a reference on how multicultural education should be implemented in Indonesia as well as a multicultural education platform in an Islamic country.